2021
DOI: 10.1016/j.mehy.2020.110452
|View full text |Cite
|
Sign up to set email alerts
|

Statins and PCSK9 inhibitors: What is their role in coronavirus disease 2019?

Abstract: Statins and proprotein convertase subtilisin/kexin type 9 (PCSK9) inhibitors interfere with several pathophysiological pathways of coronavirus disease 2019 (COVID-19). Statins may have a direct antiviral effect on severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) by inhibiting its main protease. Statin-induced up-regulation of angiotensin-converting enzyme 2 (ACE2) may also be beneficial, whereas cholesterol reduction might significantly suppress SARS-CoV-2 by either blocking its host-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 79 publications
(64 reference statements)
0
25
0
2
Order By: Relevance
“…It should be noted that statin-treated individuals are more likely to be older and to have cardiovascular risk factors or disease, and thereby more likely to have severe COVID-19 [ 3 ]. Statins seem to up-regulate angiotensin-converting enzyme 2, which could possibly enhance COVID-19 transmissibility [ 4 ]; on the other hand, these drugs present anti-oxidative, anti-inflammatory, anti-arrhythmic, anti-thrombotic properties and have beneficial effects on endothelial dysfunction, which could be proved protective against fatal respiratory, cardiovascular and thromboembolic complications in COVID-19 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that statin-treated individuals are more likely to be older and to have cardiovascular risk factors or disease, and thereby more likely to have severe COVID-19 [ 3 ]. Statins seem to up-regulate angiotensin-converting enzyme 2, which could possibly enhance COVID-19 transmissibility [ 4 ]; on the other hand, these drugs present anti-oxidative, anti-inflammatory, anti-arrhythmic, anti-thrombotic properties and have beneficial effects on endothelial dysfunction, which could be proved protective against fatal respiratory, cardiovascular and thromboembolic complications in COVID-19 [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for the differential association of SGLT2i with the risk of pneumonia versus upper or lower respiratory infection are unknown [ 2 ]. Considering the inflammatory pathways involved in the pathophysiology of pneumonia, the anti-inflammatory properties of SGLT2i may be more relevant [ 14 ]. Furthermore, pneumonia is a more objective endpoint since its diagnosis is established with imaging criteria.…”
Section: Discussionmentioning
confidence: 99%
“…The available data indicate that the use of RAAS inhibitors did not increase the risk of SARS-CoV-2 infection or cause adverse outcomes [ 40 , 81 , 83 , 84 , 85 ]. On the contrary, due to an increase in the production of angiotensin 1–7 and the catabolism of angiotensin II, ACE2 upregulation may be more helpful than harmful for patients infected with SARS-CoV-2 [ 86 , 87 ]. Evidence from cardiology showed that RAAS inhibitors such as ACEIs and ARBs can reduce the risk of thrombus formation [ 88 ].…”
Section: Therapeutic Strategiesmentioning
confidence: 99%